2023
DOI: 10.1128/msphere.00088-23
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-Dependent Biotinylation and Identification of Flagellar Proteins in Trypanosoma cruzi

Abstract: Trypanosoma cruzi is a protozoan parasite that causes Chagas disease, which causes substantial morbidity and mortality in South and Central America. Throughout its life cycle, T. cruzi interacts with insect and mammalian hosts via its single flagellum, establishing intimate contact with host membranes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
(101 reference statements)
0
6
0
Order By: Relevance
“…Using mass spectrometry, they identified 218 flagellum-enriched proteins. Among them, 40 flagellum-enriched proteins were found to occur in all life stages of two parasitic organisms, including homologs of known flagellar proteins from other trypanosome species and proteins specific to the Trypanosoma cruzi lineage [ 140 ]. Studies have shown that phase separation is involved in many important cellular processes such as RNA metabolism, signal transduction, and stress granule assembly.…”
Section: Applications Of Biotin Ligase-based Proximity Marker Technologymentioning
confidence: 99%
“…Using mass spectrometry, they identified 218 flagellum-enriched proteins. Among them, 40 flagellum-enriched proteins were found to occur in all life stages of two parasitic organisms, including homologs of known flagellar proteins from other trypanosome species and proteins specific to the Trypanosoma cruzi lineage [ 140 ]. Studies have shown that phase separation is involved in many important cellular processes such as RNA metabolism, signal transduction, and stress granule assembly.…”
Section: Applications Of Biotin Ligase-based Proximity Marker Technologymentioning
confidence: 99%
“…T. cruzi amastigote maintains elements of a motile 9+2 axoneme such as dynein arms and central pair apparatus, as shown by structural ( Fig. 1A and B ) and biochemical approaches ( 2 - 4 ), arguing in favor of a motile activity. In amastigote, it is commonly reported that the PFR is absent.…”
Section: The Surprisementioning
confidence: 90%
“…1A , arrowhead). This morphological data is strengthened by the presence of some IFT proteins (IFT81, IFT88, and IFT20) identified in amastigote during the flagellum membrane protein SMP1-1 proximity proteome ( 4 ).…”
Section: How Is the Short Motile Flagellum Constructed?mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, endogenously tagged TcCARP3 exhibited the same dual localization as TcAC1. While this manuscript was in preparation, TcCARP3 was identified by mass spectrometry in a T. cruzi fraction of enriched flagellar proteins obtained using a proximity-dependent biotinylation approach ( 54 ). These authors also reported the localization of this protein at the tip of the flagellum, as confirmed by endogenous tagging and IFA.…”
Section: Discussionmentioning
confidence: 99%